Ketaatan Pengguna Jalan dalam Tertib Berlalu Lintas di Wilayah Hukum Polresta Denpasar - Rosalina Indah Putri; I Ketut Sukadana; Ni Made Sukaryati Karma (Jurnal Konstruksi Hukum, 2021)
The order and safety of the driver is very important, one of the conditions for the driver to have a driver's license. Article 281 of the LLAJ Law clearly regulates sanctions for motorists who do not have a SIM, of course with the hope that no more traffic violations will occur. There are still many motorcyclists in the Denpasar Police jurisdiction who violate driving regulations by not having a SIM. which is an obligation for all motorists on the highway without exception. This study aims to explain the obedience of road users to Article 281 of Law Number 22 of 2009 concerning road traffic and transportation and to reveal the police's efforts to overcome the low traffic compliance of motorized vehicle users in the jurisdiction of Denpasar City. This research is designed with empirical legal research with a Legislative approach. The data used are primary and secondary materials obtained through interviews and documentation. the data is processed quantitatively in tabular form and analyzed qualitatively. Obedience of road users to Article 281 of Law Number 22 of 2009 concerning Road Traffic and Transportation, is still very lacking, this is due to the lack of awareness of road users, so they are still very dismissive and negligent in making driving licenses. Police efforts in overcoming the low traffic compliance of motorized vehicle users in the jurisdiction of Denpasar City, namely providing an introduction to traffic order from an early age to children, counseling and socialization, especially to students, students and directions to Banjar residents, as well as delivering orderly information. traffic and the development of the situation on the highway through social media.